Analytic Hierarchy Process for Decision Making in Asset Integrity Program: Route for Pipeline Corridor - Mairudi, Mairudi; Novani, Santi (The Indonesian Journal of Business Administration, 2016)
Abstract. pt chevron pacific indonesia (cpi) operates 90 fields in sumatra with two main squares, duri and minas. most of oil pipelines from minas to duri have being services more than 50 years and have severe external corrosion. in addition, community encroachment directly on top of the pipelines has escalated over the last decade. the pipeline has inadequate physical protection and a high risk of damage and or failure from public interaction, such as traffic crossing or collision as well as the risk of oil theft. project team has initiated a pipeline integrity project to replace the aging pipe and relocate the pipeline to avoid populated area. the purpose of this final assignment is to select the best route alternative for pipeline corridor from minas to duri in chevron sumatra operation. the end objective of this route selection is to minimize chevron facilities impacts to community and also to protect chevron facilities from community. the decision making process is to select the best route use value-focused thinking (vft) and analytic hierarchy process (ahp) that involving multiple objectives. vft method is applied to generate alternatives and criteria, while the ahp method will determine the best alternative. decision-making is done through small focus group discussion by five multi discipline engineers who have knowledgeable and experience related with the project. the selected route for new pipeline corridor is thru the power line route. the selection process has considered cost (piping and civil) and non cost (technical, environmental and social). sensitivity analyses were conduct on this route alternatives and obtained consistent result. the powerline route (score 0.415) is as the first route priority, the highway route (score 0.167) in the second and the cpp line route (0.166) in the third route priority. the selected route will align with the company objective to protect the pipeline facilities from the community and also protect the community from the pipeline facilities along the new corridor.keywords: pipeline integrity project,best route alternative, decision making process, ahp, vft